STUDY OF THE EARTH’S CRUST AND UPPER SHELL WITH THE HELP OF GEOPHYSICAL FIELD VARIATIONS (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
In the article the analysis of the relationship between aperiodic variations of geophysical fields and neotectonic processes observed on geodynamic testing polygon in the Republic of Armenia. The analysis makes it possible to highlight certain active zones where there is a definite correlation relationship. The study of field variations will enable the prediction of volcanic and seismic phenomena that are the results in the marked variations.
Keywords: variation; neotektonika; geophysical fields; correlation